Profile and prognostic value of tumour-infiltrating lymphocytes in triple-negative breast cancer in women in Kinshasa at CUK, Democratic Republic of the Congo - ILENGA MATUMONA, Willems; Kilara, Tarcisse K.; Pholo, Jean Paul M.; Kaswiji, Fraste M.; Lebwaze, Massamba Bienvenu; Chirimwami, Raphael B. (Orapuh Journal, 2025)
Introduction Triple-negative breast cancer (TNBC), known for its particularly aggressive nature, is associated with a poor prognosis. Tumour-infiltrating lymphocytes (TILs) are emerging as a key prognostic biomarker in this subtype. Purpose To quantitatively analyse TILs and explore their association with clinical and pathological characteristics among Congolese patients. Methods A cross-sectional, descriptive study was conducted between January 2022 and December 2024 in two reference cytopathology laboratories in Kinshasa (University Clinics and LEBOMA Pathology Cabinet). A convenience sample of 147 breast cancer patients was included, of whom 28 had triple-negative breast cancer confirmed by immunohistochemistry. Data were extracted using Microsoft Excel 2016 and analysed with SPSS version 27. Proportion comparisons were performed using the chi-square test, with statistical significance set at p < 0.05. Results Among the 147 breast cancer patients included, 28 (19.05%) had TNBC. The intermediate TIL group was the most represented (39.3%), predominantly associated with grade 3 tumours, followed by the low TIL group (35%), where grade 2 tumours predominated (60%). The age group ≤ 50 years accounted for 19 patients (67.9%), among whom 9 (47.3%; 95% CI [27.3–68.3]) had intermediate TILs. A low degree of TILs was observed in 6 patients (66.7%) aged > 50 years. A Ki-67 proliferative index > 30% was noted in 21 patients (75%), of whom 10 (47.6%; 95% CI [28.3–67.6]) had intermediate TILs. Conclusion The majority of TNBC patients had TIL levels ≥10. High TIL density was associated with younger age and a lower Ki-67 proliferation index. TIL assessment therefore emerges as a relevant prognostic biomarker that could guide patient follow-up and therapeutic decision-making, particularly regarding immunotherapy.